Participação e protagonismo de mulheres na comunhão episcopal internacional na cidade de Recife no século XXI: estudo à luz do movimento de Jesus do primeiro século. - Costa, Marcos Paulo Fonseca da (2022)
It is common knowledge that many women in Brazil suffer from domestic violence, head households alone and earn lower wages than men, even though they have the same qualifications and experience. The objectives of this work were, depending on the obstacles listed, to study the participation and protagonism of women in faith communities of the International Episcopal Communion in the city of Recife (CEI/Recife) in the 21st century, to investigate what kind of relationship the Jesus movement inaugurated with the women who participated in it and to analyze to what extent the understanding of the presence of women in the Jesus movement in the First Century can contribute to a critical look at the condition of women in the CEI/Recife today. To this end, eleven volunteers answered, between April 2020 and December 2021, a questionnaire on issues related to the role of women in the CEI/Recife, we investigated the performance of women in the CEI/Recife, presenting aspects that demonstrated their real situation and condition in these faith communities. We also study traits of the valorization of women in the Jesus movement, which demonstrate their welcoming perspective and, in addition, we deepen elements that contributed to the protagonism of women in the CEI/Recife, in the light of the understanding of the Jesus movement. The authors chosen for the theoretical foundation were: Gerd Theissen, Wolfgang Stegemann, Ekkehard Stegemann and Elisabeth Fiorenza. As the main result of the research, we found a tension between certain answers given by the eleven collaborators and the reality experienced by them: some responded that the CEI/Recife encourages the exercise of leadership by women, but only one of them occupies a leading role. in the Church – participation in the Ecclesial Board. In other words, although women act on several fronts in faith communities, within the scope of this research it was not possible to verify the effective role of women in the CEI/Recife.